CHARACTERIZATION OF WATER-ETHANOL EXTRACTS OF BLACK WALNUT LEAF (JUGLANS NIGRA L.) - Rajković, Katarina; Vasić, Marijana; Simić, Valentina; Radovic, Nikolina; Milovanović, Brankica; Đokić, Brankica (ACADEMIC REVIEW, 2019)
In this paper, black walnut leaf extracts were prepared by ultrasonic extraction using water-ethanol solvents of different concentrations (0 - 96% (v / v)). The total extraction yield ranged from 0.019 to 0.034 mg cm-3. The content of total polyphenols ranged from 0.001 to 0.005 mgGAE cm-3. The highest value of extraction yield and total polyphenol content was 0.034 mg cm-3and 0.005 mg GAE cm-3 in 50% water-ethanol extract. Determination of total polyphenol content has shown that black walnut leaf is a rich source of polyphenolic compounds and can be used as a natural source of antioxidants.